REM sleep behaviour disorder in essential tremor: A polysomnographic study. (23rd April 2020) - Bugalho, Paulo; Salavisa, Manuel; Borbinha, Cláudia; Fernandes, Marco; Meira, Bruna; Barbosa, Raquel; Mendonça, Marcelo
Abstract: Our objectives were to assess the prevalence of REM sleep behaviour disorder in patients with Essential Tremor, using video‐polysomnography and to compare REM sleep behaviour disorder features in essential tremor with those of patients with alpha‐synucleinopathies. Forty‐nine patients with essential tremor were screened with the REM Sleep Behaviour Disorder Screening Questionnaire. Patients scoring positive and those with spontaneous complaints of REM sleep behaviour disorder ( n  = 6) underwent video‐polysomnography. The clinical features of essential tremor were compared between patients with and without REM sleep behaviour disorder. Video‐polysomnography data were compared between patients who had essential tremor and Parkinson's disease with REM sleep behaviour disorder and those with idiopathic REM sleep behaviour disorder. Fourteen patients (23.5%) screened positive for REM sleep behaviour disorder, confirmed by video‐polysomnography in five (11.6%). All patients with essential tremor and REM sleep behaviour disorder had rest tremor, compared with 13 (34.2%) in the group with essential tremor but without REM sleep behaviour disorder ( p  = .009). In video‐polysomnography, patients with essential tremor and REM sleep behaviour disorder were similar to patients with Parkinson's disease with REM sleep behaviour disorder and presented worse sleep dysfunction and lower severity of REM sleep behaviour disorder compared to those with idiopathic REM sleep behaviour disorder. We found a high prevalence of REM sleep behaviour disorder in patients with essential tremor, associated with a predominance of rest tremor. Polysomnography data from patients with essential tremor and REM sleep behaviour disorder were similar to those in patients with Parkinson's disease. This suggests a relation between this subgroup of patients with essential tremor and the alpha‐synucleinopathies.